2020
DOI: 10.3389/fcell.2020.00455
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stem Cell Extracellular Vesicles as a “Holistic” Approach to CNS Repair

Abstract: Neurodegeneration is a hallmark of many diseases and disorders of the central nervous system (CNS). High levels of neuroinflammation are often associated with irreparable damage to CNS cells due to the dysregulation of signaling cascades that are unable to restore a homeostatic balance. Due to the inherent complexity of the CNS, development of CNS-related therapeutics has met limited success. While stem cell therapy has been evaluated in the context of CNS repair, the mechanisms responsible for their functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 193 publications
(252 reference statements)
0
21
0
Order By: Relevance
“…Here specifically, we were interested in examining the functional effects of stem cell EVs on HIV-1 infected neurospheres. Our rationale was based on the results from numerous studies which have highlighted the protective and reparative properties of stem cell EVs among various CNS pathologies, as reviewed elsewhere [42,46,47,132].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here specifically, we were interested in examining the functional effects of stem cell EVs on HIV-1 infected neurospheres. Our rationale was based on the results from numerous studies which have highlighted the protective and reparative properties of stem cell EVs among various CNS pathologies, as reviewed elsewhere [42,46,47,132].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for a "holistic" reparative approach to potentially control cellular damage and regulate inflammation. There is mounting evidence that EVs from different sources of stem cells, namely MSCs and iPSCs, possess broad reparative and regenerative properties across various pathologies, including those related to the CNS [42,43,44,45,46,47]. Whether or not these vesicles confer reparative effects in the context of infection remains relatively unexplored, especially with respect to the CNS.…”
Section: The Effect Of Stem Cell Evs On Hiv-1 Infected Neurospheresmentioning
confidence: 99%
“…It has been reported that between 30 and 80% of protein-coding genes are regulated by miRNA. This is primarily achieved through the complementary binding of miRNA to a target mRNA sequence, resulting in either mRNA degradation or translational repression [ 166 ]. Circular RNA (circRNA) are closed-loop structures representing a unique class, highly stable form of non-coding RNA present in EVs [ 167 ].…”
Section: Beginning Of the Era Of Therapy Based On Secretome Of Mscmentioning
confidence: 99%
“…Exosomes have recently been investigated in many studies as a suitable alternative for the shortcomings of traditional agents due to their biological compatibility and particularly small size ( Arrighetti et al, 2019 ) for brain targeting ( Lapchak et al, 2018 ; Qu et al, 2018 ). Experimental studies provide new insight that exosomes and their cargo play important roles in nerve regeneration, synaptic function, plasticity, immune response, and exosome-mediated intercellular communication, contributing to brain reconstruction ( Qing et al, 2018 ; Liu et al, 2019 ; Branscome et al, 2020 ). Exosomes’ BBB crossing ability opens new getaways to the CNS, targeting the treatment of various neurodegenerative disorders, such as stroke, Alzheimer’s disease, tumors, and autoimmune diseases ( Abbott et al, 2006 ; Andreone et al, 2015 ).…”
Section: Exosomes’ Natural Brain Targeting and Homing Abilitiesmentioning
confidence: 99%